Pendekatan Konstruktivisme dalam Kebijakan Pembelajaran Berbasis Proyek: Transformasi Pendidikan Menuju Kreativitas dan Kolaborasi - Pratami, Risti (Universitas Airlangga, 2024)
This research seeks to provide practical and theoretical guidance in the context of developing educational policies that always support positive transformations in the context of the learning process that uses the constructivism approach. This research is a qualitative research with a descriptive approach using secondary data sourced from books, the internet, and journals. Based on the results of the literature review from various sources, it shows that the constructivism approach in project-based learning not only pays attention to the needs of each student, but it is also relevant to educational policies that emphasize aspects of creativity, inclusion, independence, collaboration, and preparation of students in facing global challenges. The implementation of this policy reinforces a holistic vision of education that unites practical knowledge with 21st century skills development in line with national education goals. This is in accordance with Law No. 20/2003 on the National Education System in Indonesia which is oriented towards the importance of developing students' potential according to their interests and talents in order to optimally achieve national education goals. Keywords: Education Policy, Constructivism Approach, Project-based Learning